2015
DOI: 10.1016/j.scico.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of refactoring on change and fault-proneness in commercial C# software

Abstract: Refactoring is a process for improving the internal characteristics and design of software while preserving its external behaviour. Refactoring has been suggested as a positive influence on the long-term quality and maintainability of software and, as a result, we might expect benefits of a lower future change or fault propensity by refactoring software. Conversely, many studies show a correlation between change and future faults; so application of a refactoring may in itself increase future fault propensity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…This is especially true for some specific code smell types, such as Message Chains [35]. The results achieved in the paper mentioned above have been confirmed by Gatrell and Counsell [37], who quantified the effect of refactoring on change-and fault-proneness of classes. The authors monitored a commercial C# system for one year, detecting the refactoring operations applied during the first four months, and examining such refactored classes for the second four months in order to determine whether and to what extent the refactoring actually produces classes having lower change-and fault-proneness.…”
Section: Impact Of Code Smells On Non-functional Attributes Of Sourcesupporting
confidence: 57%
“…This is especially true for some specific code smell types, such as Message Chains [35]. The results achieved in the paper mentioned above have been confirmed by Gatrell and Counsell [37], who quantified the effect of refactoring on change-and fault-proneness of classes. The authors monitored a commercial C# system for one year, detecting the refactoring operations applied during the first four months, and examining such refactored classes for the second four months in order to determine whether and to what extent the refactoring actually produces classes having lower change-and fault-proneness.…”
Section: Impact Of Code Smells On Non-functional Attributes Of Sourcesupporting
confidence: 57%
“…Palomba et al [26] confirmed such findings on a larger set of 13 code smell types, and also reported that the removal of code smells might be not always beneficial for improving source code maintainability. Also Gatrell and Counsell [62] and by Li and Shatnawi [63] confirmed the negative impact of code smells on faultproneness; in addition, they suggested that refactoring a class, besides improving the architectural quality, reduces the probability of the class having errors in the future [62], [63].…”
Section: Related Literature On Code Smellsmentioning
confidence: 92%
“…Gatrell and Counsell [24] conducted an empirical study aimed at quantifying the effect of refactoring on class changeand defect-proneness. In particular, they monitored a commercial project for eight months and identified the refactoring operations applied by developers during the first four months.…”
Section: B Change-and Defect-proneness Of Code Smellsmentioning
confidence: 99%
“…To fill this gap, in this paper we quantitatively investigate the relationship between the presence of smells in test methods and the change-and defect-proneness of both these test methods and the production code they intend to test. Similar to several previous studies on software quality [24], [62], we employ the proxy metrics change-proneness (i.e., number of times a method changes between two releases) and defectproneness (i.e., number of defects the method had between two releases). We conduct an extensive observational study [15], collecting data from 221 releases of ten open source software systems, analyze more than a million test cases, and investigate the association between six test smell types and the aforementioned proxy metrics.…”
Section: Introductionmentioning
confidence: 99%